Ideologia bolivariana : as apropriações do legado de Simón Bolívar em uma experiência de povo em armas na Venezuela : o caso da Guerra Federal (1858-1863) - Ferreira, Carla Cecilia Campos (2006)
This research analyzes the Bolivarian historical ideology since the Simon Bolívar death in 1830 until the end of the 20th Century, focusing on the development of what we shall call social consciousness practices in an experience of popular armed confrontation: The Venezuela’s Federal War of 1858-1863. Our aim was to understand and evaluate the potentialities of the historical memory as a social and emancipatory mobilization practice. In order to conduct the research and guided by the available documents and other historical sources, we did characterized "bolivarianism" as a revolutionary-romantic ideology, with a special and contradictory unity between revolution and conciliation. The research has revealed that Bolivar’s project of creating Gran Colombia was a relevant part of the Federal War political proposal. Bolivarianism was also a general ideological reference to important individuals during the Federal War. Finally, the study brought new evidence and insight regarding the nexus between historical memory and ideology as an activity of remembrance in an operative present, which helps to explain how the past is selected through conflicting projects of future.